2019
DOI: 10.3389/fvets.2019.00247
|View full text |Cite
|
Sign up to set email alerts
|

Serum Vitamin D Metabolites and CXCL10 Concentrations Associate With Survival in Dogs With Immune Mediated Disease

Abstract: Background: Low vitamin D increases the risk of immune-mediated disease (IMD) in human beings and rodent models. Vitamin D metabolites, particularly 1,25(OH)2D3, modulate gene expression of immune cells and may attenuate immune pathways that drive IMD. Hypothesis/objectives: Our primary hypothesis was that serum 25(OH)D3 and 1,25(OH)2D3, are reduced in patients with IMD and associate with poorer outcomes. We secondarily hypothesized serum 24,25(OH)2D3 would not be associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…8 The primary circulating metabolite of vitamin D, 25-hydroxyvitamin (OH)D, has been established as a useful biomarker in dogs to predict outcome in various disease processes. [9][10][11][12][13] However, the role of vitamin D in shelter dogs with CIRDC remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…8 The primary circulating metabolite of vitamin D, 25-hydroxyvitamin (OH)D, has been established as a useful biomarker in dogs to predict outcome in various disease processes. [9][10][11][12][13] However, the role of vitamin D in shelter dogs with CIRDC remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…A second mechanism might be the potential of macrophages to convert 25OHD3 to 1,25(OH)2D3. 25OHD3 can be converted into 1,25(OH)2D3 by macrophages or other cells that express 1α-hydroxylase [72,73]. A study that proved correlation of VDBP polymorphisms with lung cancer was conducted among Thai patients.…”
Section: Lung and Colorectal Cancermentioning
confidence: 99%
“…No reference range exists for 3-epi-25(OH)D3 in humans, therefore data from a systemic review which reported ranges from several studies was used (see Bailey et al (2013) [ 79 ]). The number of studies included to provide data for each of the veterinary species are as follows: ( A ) dogs n = 8 [ 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 ], cats n = 1 [ 85 ], horses n = 1 [ 88 ], sheep n = 4 [ 30 , 89 , 90 , 91 ], cattle n = 2 [ 92 , 93 ], pigs n = 1 [ 94 ], poultry n = 2 [ 95 , 96 ] and nonhuman primates n = 2 [ 97 , 98 ]; ( B ) dogs n = 2 [ 81 , 85 ] and cats n = 1 [ 85 ]; and C . dogs n = 1 [ 83 ].…”
Section: Figurementioning
confidence: 99%